ANÁLISE DA INCIDÊNCIA DE QUADROS DE BRADICARDIA EM PACIENTES ANESTESIADOS: ESTUDO RETROSPECTIVO - da Silva, Taiza; Moreira Silva, Ana Clara; Rodrigues Barbosa Ferreira, Ana Flávia; da Silva Gonçalves, Larissa; Barboza Alves, Karoline; Ferreira de Oliveira, Nayara Cristina; Antunes de Lima, Marcos Paulo (Sinapse Múltipla, 2023)
Não se aplica